“The Own-The Borrowed” in Artistic Culture of the 20th-21st Centuries - Anfilova, Svitlana; Kucherenko, Stanislav; Mizitova, Adilya; Pidporinova, Kateryna; Sediuk, Igor (Journal of History Culture and Art Research, 2020)
The article presents various forms of working with the “borrowed” material in the artistic practice of recent centuries. This phenomenon covers painting, literature, cinema, choreography, and music. The stable nature of this phenomenon, preserved by a tradition, is explained by its ability to identify the author’s position towards the current needs of the time in comparison with another creative consciousness, an understanding of the world order, as well as the artistic and aesthetic priorities. A dialogue with the “borrowed” thought plays a significant role in the art of music. Some special ways of work in the conditions of “the own – the borrowed” concept emerged here, and each of them caused the certain genres to appear. In real practice, the following genres were firmly established: transcription, adaptation, arrangement, and paraphrase. Despite the internal differences, the general reflection of the author’s individual creative approach and, indirectly, self-awareness of the specific historical stage in the cultural development remains their common feature. “The own – the borrowed” concept, containing two opposing ideas, reveals the inconsistency of artistic and aesthetic processes in the historical development of the ballet genre, the complex interaction of classic dance with inapplicative symphonic music, and the relation of dance and flexibility in choreographic drama. In whatever form of art the “borrowed” material is used, including the genres of a “light” music, the ludic logic inevitably actualizes itself, starting from the choice of an object for a creative “duel” and ending with a combination of language means. The competitive atmosphere explains both the repeated use of the same material by the artists of different generations, as well as the appearance of peculiar “shifters” who, introducing an ironic and comedic element, represent the skillful mastery. Thanks to this, working with a “borrowed” material retains its value regardless of the change in artistic and aesthetic paradigms.